Development of a new CAD-method for Tool CAE-analysts at Gestamp HardTech - Andersson, Erika; Al-shatrawi, Zeinab (2016)
This project is a Master of Science thesis in industrial design engineering at Luleå University of Technology. It was conducted by Zeinab Al-shatrawi and Erika Andersson in cooperation with Gestamp HardTech R&D in Luleå during the spring semester of 2016.Gestamp HardTech is a world leading company in the press-hardening technology. They manufactures and delivers car components such as side impact beams, bumpers, A-pillar and B-pillar. They also develop and manufacture the production tools for the components. Tool CAE-analysts at the Research and Development Center in Luleå develops components and tools. Their work consists of modelling and simulations in order to create forming specifications and tooling specifications for the products. The Tool CAE-analysts either uses the product development software NX or CATIA V5. The Tool CAE-analysts that uses CATIA V5 share a common CAD-method and uses automated features to speed up and structure their work. There are no common CAD-method or automated features in NX so each Tool CAE-analyst has created their individual CAD-method.The objectives in this project was to develop a new common CAD-method and to identify suitable features to automate that are beneficial for the Tool CAE-analysts that uses NX. The automations allows the product development software to create the work. The purposes of the new CAD-method and automations are to structure and standardize their work process. Standardization in their work can increase the quality, make their development process more time-efficient and facilitate their teamwork.The project started by studying the assignment and analyzing the background. This information was used to plan and structure the process. The project continued with a literature study that included studies of previous theses at Gestamp HardTech and studies of the areas industrial design engineering, method objectives, organizing tools in NX and automation tools in NX. The literature study continued throughout the whole project process.Tool CAE-analysts were ...